Connecting Habitats: Modelling Landscape Connectivity for Large Mammals in Omo-Shasha-Oluwa Forest Reserves, South-West Nigeria - Fasona Michelle I.; Okimiji Princess O.; Soneye Alabi S.O.; Gregory Andrew J.; Egonmwan Rosemary I. (Journal of Landscape Ecology, 2024)
Preserving landscape connectivity in the Omo-Shasha-Oluwa Forest Reserves is crucial due to human-induced fragmentation, shrinking habitats, and disrupted migration routes for wildlife. From 2014 to 2016, we conducted surveys to gather large mammal presence data, mapping their distribution using the MaxEnt algorithm. Employing Circuitscape software and circuit theory concepts, we predicted connectivity patterns for six large mammal species. Our results consistently showed robust predictive performance, with Area Under the Curve (AUC) values exceeding 0.75 for species distribution models. Notably, we identified suitable habitat patches for seven key species, spanning 1760 km2 for C. civetta, 1515 km2 for T. Scriptus, 729 km2 for L. cyclotis, 1693 km2 for P. porcus, 1350 km2 for C. mona, 1406 km2 for P. maxwellii, and 1379 km2 for C. torquatus. Our analysis highlighted distance to human settlements as the most significant predictor for habitat models concerning T. Scriptus, C. civetta, P. maxwellii, C. torquatus, P. porcus, and C. mona, whereas land use type emerged as a critical factor for L. cyclotis. Furthermore, examination of maximum current flow patterns revealed varying degrees of connectivity among habitat patches, indicating potential bottlenecks to species movement, particularly across major rivers and in areas affected by human activities. These findings offer crucial insights for conservation efforts, guiding strategies to preserve wildlife metapopulation dynamics in the Omo-Shasha-Oluwa Forest Reserves landscape